MICRO ECONOMIC IMPACTS OF INTERNATIONAL MIGRATION - Alam, A.S.A Ferdous; Begum, Halima; Siwar, Chamhuri; Talib, Basri; Bhuiyan, Md. Anowar Hossain; Elfithri, Rahmah (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
International migration is one of the key components of local economic development in a labour sending country. The returns of migration and remittances play a significant role in the economic development and growth of the source country. The remittance causes a positive Balance of Payment as well as poverty reduction in Bangladesh. These international migrations also have impacts on micro economic issues like local and household economy, which havereceived very little attention in existing studies. Therefore, to check the issue, this study collected primary data based on a questionnaire survey from 306 Bangladesh workers who are engaged in wage-earning employment in Malaysiaduring the period of Nov-Dec 2010. This study analysed the data based on the Path Measurement Model. This empirical study found that international migration significantly improves the micro economy of Bangladesh such ashouse ownership, improvement of economic conditions, donation towards local institutes and infrastructure, new work experience, new skills, and poverty reduction. Some initiatives such as communication skills, maintaining andimproving economic diplomacy and discouraging the Hundi System (Illegal remittance transfer system) are suggested to improve these rising consequences of international migration in Bangladesh.